Răspuns :
(a+b)/(a×b) = 1/a + 1/b
__________________
Fie 1/a + 1/b
se aduce la acelasi numitor
b/(a×b) + a/(b×a) = (a+b)/(a×b)
(a-b)/(a×b)=1/a - 1/b
__________________
Fie 1/a - 1/b
se aduce la acelasi numitor
b/(a×b) - a/(b×a) = (a-b)/(a×b)
__________________
Fie 1/a + 1/b
se aduce la acelasi numitor
b/(a×b) + a/(b×a) = (a+b)/(a×b)
(a-b)/(a×b)=1/a - 1/b
__________________
Fie 1/a - 1/b
se aduce la acelasi numitor
b/(a×b) - a/(b×a) = (a-b)/(a×b)
1 / a + 1 / b = b / ( a x b ) + a / ( a x b ) = ( b + a )/ ( a x b)= ( a + b ) / (a x b )
→ b + a = a + b ⇔ adunarea este comutativa
1 / a - 1 / b = b / ( a x b ) - a / ( a x b ) = ( b - a ) / ( a x b ) → c.c.t.d.